The fold - Clines, Peter, 1969- (Crown Publishers, 2015)
An old friend presents Mike Erikson with an irresistible mystery to solve -- far out in the California desert, a team of DARPA scientists has invented a device that shrinks distances so that a traveler can travel hundreds of feet with a single step but evidence is mounting that this miraculous machine isn't quite what it seems--and that its creators are harboring a dangerous secret.